Sistem Kontrol Playlist Pada Radio Citis Fm Berbasis Android - Wahyudy, Dzulmy; Aswandi, Aswandi; Jamilah, Jamilah (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2022)
The development of science and technology cause humans always keep learning and looking for a way for the application of SCIENCE and TECHNOLOGY can provide many benefits and lighten the workload for humans. Development of communication media, especially broadcast media, i.e. radio and television is one of the most efficient forms of mass media in conveying information. Controlling playback of playlist on the radio it takes application of remote desktop technologies, to improve the quality of networks on the system as well as the application of the technology of the remote system to be built. The research aims to find out the quality of networks on the system using the method of QoS and the speed of response when the operator controlling using the remote on the system. In this study used QoS method as a parameter testing system. Data collected by doing a test run on a system that has been built. Testing done against delay, average – flat on a range of "Good" on a vulnerable time 0 – 5 ms/s, average throughput testing – flat on a range of "Medium" with the standardization of 50%, for testing packet loss is on the "excellent" range. Based on data analysis, it turns out that the quality of the network included in the categories of "less than Satisfactory", with the success rate of the system reach 74.75%.Keywords: Radio, Streaming, QoS